Protective Effect of Punica granatum L. against Serum/Glucose Deprivation-Induced PC12 Cells Injury. (7th July 2013) - Forouzanfar, Fatemeh; Afkhami Goli, Amir; Asadpour, Elham; Ghorbani, Ahmad; Sadeghnia, Hamid Reza
Abstract : The discovery and development of natural products with potent antioxidant, anti-inflammatory, and antiapoptotic properties have been one of the most interesting and promising approaches in the search for the treatment of many neurodegenerative diseases including ischemic stroke. Serum/glucose deprivation (SGD) has served as an excellent in vitro model for the understanding of the molecular mechanisms of neuronal damage during ischemia and for the development of neuroprotective drugs against ischemia-induced brain injury. Recent studies suggested that pomegranate ( Punica granatum L.) or its active constituents exert pharmacological actions such as antioxidant, anti-inflammatory, and neuroprotective properties. Therefore, in this study we investigated the possible protective effects of different extracts of pomegranate against SGD-induced PC12 cells injury. Initially, the cells were pretreated with different concentrations of pulp hydroalcoholic extract (PHE), pulp aqueous extract (PAE) and pomegranate juice (PJ) for 2 h and then deprived of serum/glucose (SGD) for 6 and 12 h. SGD caused a significant reduction in cell viability (measured by the MTT assay) after 6 and 12 h, as compared with control cells (P < 0.001 ). Pretreatment with PHE, PAE, and PJ significantly and concentration-dependently increased cell viability following SGD insult for 6 and 12 h. A significant increase in DNA damage (measured by the comet assay) was seen in nuclei of cells following SGD for 12 h (P < 0.001 ). In control groups, no significant difference was seen in DNA damage between PHE, PAE, and PJ-pretreated and vehicle-pretreated PC12 cells (P > 0.05 ). PHE, PAE, and PJ pretreatment resulted in a significant decrease in DNA damage following ischemic insult (P < 0.001 ). This suppression of DNA damage by PHE, PAE and PJ was found to be concentration dependent. These data indicate that there is a cytoprotective property in PHE, PAE, and PJ under SGD condition in PC12 cells, suggesting that pomegranate has the potential to be used as a new therapeutic strategy for neurodegenerative disorders.